IMPLEMENTATION OF STRATEGIC PLANS (RENSTRA) AT THE PANCA BHAKTI PONTIANAK HIGH SCHOOL OF HEALTH SCIENCES - Rinto, Petrus; Radiana, Usman; Wicaksono, Luhur; Asrori, M; Yani. T, Ahmad (Universitas Tanjungpura, 2025)
This research aims to obtain objective information and describe the implementation of the Strategic Plan at the Panca Bhakti Pontianak College of Health Sciences, which includes: The process of preparing the Strategic Plan, Implementing the Strategic Plan, evaluating the Strategic Plan, as well as supporting and inhibiting the implementation of the Strategic Plan. The form of research used is qualitative, with descriptive methods. The research subjects were 6 people consisting of: (1) Deputy Head 1, 38 years old, female, and leadership elements. (2) Deputy Deputy 2, 49 years old, female, and a leadership element. (3) Personnel field, 29 years old, female, waket 3 staff. (4) Head of Midwifery Study Program, 29 years old, female, lecturer. (5) Head of LPPM and PKM, 48 years old, male, lecturer. (6) Head of HRD, 59 years old, male, lecturer. The data collection method in this research was obtained through observation, in-depth interviews, and document analysis and triangulation. The main finding in this research is that the institutional Strategic Plan focuses more on implementing the Tri Dharma in higher education, while the emphasis is more on lecturers as implementers of the Tri Dharma. This is reflected in the results of interviews and institutional performance accountability reports, where the implementation shows results in the good category. The research results concluded that the process of preparing the Strategic Plan had been carried out through a series of systematic and participatory stages. The implementation of the Strategic Plan is more directed at implementing the Tri Dharma, with more emphasis on lecturers as implementers of the Tri Dharma. The supporting factor lies in the leadership, and all obstacles are always discussed. The implication is that previous research on strategic plans found that institutional strategic plans were only a dead book, but the strategic plan at STIKES Panca Bhakti Pontianak was the main guide in implementing the institution's Tri Dharma.